Overview of Student Interest in Pencak Silat Extracurricular at MTSN 2 Solok - Kurnia, Bambang Depi; Kiram, Yanuar; Sin, Tjung Hauw; Haryanto, Jeki (Jurnal Gladiator, 2022)
One type of interest is individual interest, this interest develops over time and is a relatively enduring tendency to be present in objects, events, ideas, etc. It is associated with positive feelings, increased value, and knowledge. Individual interests energize and motivate their thoughts and actions in a highly goal-directed manner. This study aims to describe students' interest in Pencak Silat extracurricular at MTSN 2 Solok. This research uses quantitative method with descriptive type. The research sample was 165 students of MTsN 2 Solok grade 8 who were taken randomly in each class from 8 A to 8 I. The data collection tool used was a questionnaire. The data analysis technique uses PAP data analysis (Banner Reference Assessment). The results showed that the description of students' interest in Pencak Silat extracurricular at Mtsn 2 Solok was as many as 6 students (3.64%) had very low interest categories, as many as 42 students (25.5%) with low categories, as many as 74 students. students (44.8%) in the medium category, as many as 34 students (20.6%) in the high category, and as many as 9 students (5.45%) in the very high category. Based on the description of the table above, it can be concluded that most of the students' individual interest in pencak silat extracurricular is in the medium category.